Implementing a Pharmacist-Led Medication Management Pilot to Improve Care Transitions - Rachel Root, PharmD, MS; Pamela Phelps, PharmD, FASHP2; Amanda Brummel, PharmD; Craig Else, PharmD, MBA (University of Minnesota Libraries Publishing, 2012)
Purpose: The purpose of this project was to design and pilot a pharmacist-led process to address medication management across the continuum of care within a large integrated health-system.Summary: A care transitions pilot took place within a health-system which included a 150-bed community hospital. The pilot process expanded the pharmacist's medication management responsibilities to include providing discharge medication reconciliation, a patient-friendly discharge medication list, discharge medication education, and medication therapy management (MTM) follow-up.Adult patients with a predicted diagnosis-related group (DRG) of congestive heart failure or chronic obstructive pulmonary disease admitted to the medical-surgical and intensive care units who utilized a primary care provider within the health-system were included in the pilot. Forty patients met the inclusion criteria and thirty-four (85%) received an intervention from an inpatient or MTM pharmacist. Within this group of patients, 88 drug therapy problems (2.6 per patient) were identified and 75% of the drug therapy recommendations made by the pharmacist were accepted by the care provider. The 30-day all-cause readmission rates for the intervention and comparison groups were 30.5% and 35.9%, respectively. The number of patients receiving follow-up care varied with 10 (25%) receiving MTM follow-up, 26 (65%) completing a primary care visit after their first hospital discharge, and 23 (58%) receiving a home care visit.Conclusion: Implementation of a pharmacist-led medication management pilot across the continuum of care resulted in an improvement in the quality of care transitions within the health-system through increased identification and resolution of drug therapy problems and MTM follow-up. The lessons learned from the implementation of this pilot will be used to further refine pharmacy care transitions programs across the health-system.